Protein carbonyls and traditional biomarkers in pigs exposed to low-dose γ-radiation - Smutná, Miriam; Beňová, Katarína; Dvořák, Petr; Nekvapil, Tomáš; Kopřiva, Vladimír; Maté, Dionýz (Research in veterinary science, 2013)
Response of pigs to irradiation manifested by production of protein carbonyls and adaptable enzymes was studied in two experiments. In one experiment, 10 mixed-sex pigs were exposed to 0.5 Gy whole body (60)Co irradiation. In the other experiment, another batch of 10 pigs was exposed to 1.0 Gy half-body irradiation. Unlike those exposed to half-body irradiation, the pigs exposed to whole-body irradiation showed significant increase in protein carbonyls by 73%, and a decrease in cholesterol by 25.7%, compared to the control group. In both cases of dose-dependent irradiation exposure, pigs showed a decrease in alanine aminotransferase activity compared with the control group. At the dose of 1 Gy, ALT activity decreased significantly by 27.7%. Aspartate aminotransferase activity in pigs after half-body irradiation decreased significantly by 65.5%. Although low doses of ionizing radiation were applied, monitoring of the above biochemical parameters helped define the pigs' biological response.
Keywords: Swine; Female; Protein Carbonylation; Animals; biologické markery; ženské pohlaví; vztah dávky záření a odpovědi; záření gama; mužské pohlaví; Biomarkers; Dose-Response Relationship, Radiation; zvířata; Gamma Rays; Male; prasata; karbonylace proteinů